1990
DOI: 10.1002/pros.2990170405
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study of androgen receptor in benign hyperplastic and cancerous human prostates

Abstract: Androgen receptor was detected immunohistochemically in benign as well as malignant prostatic tissues by using a monoclonal rat anti-human androgen receptor antibody (AN 1-15). In both benign and malignant cells, the androgen receptor was exclusively localized in nuclei. In hyperplastic prostate, the androgen receptor was stained in the glandular and the stromal cells. In the gland, cells facing the lumen were stained more intensively than those adjacent to the basal membrane. In cancer tissue, receptor-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 38 publications
7
49
0
3
Order By: Relevance
“…The high response rate is in accordance with the observation that most human prostate cancers have a high content of androgen receptors (AR; Martelli et al 1980;Concolino et al 1982). Some recent immunohistochemical studies using antibodies to the amino-terminal domain of AR revealed that the proportion of AR positive tumour cells varied among prostate cancers; poorly differentiated prostate cancers tended to have a diminished proportion of AR positive tumour cells (Ruizeveld de Winter et al 1990;Masai et al 1990). In ligand binding studies on tumour cytosols, Gorelic et al (1987) similarly noted heterogeneity of AR expression Correspondence to: T.H.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The high response rate is in accordance with the observation that most human prostate cancers have a high content of androgen receptors (AR; Martelli et al 1980;Concolino et al 1982). Some recent immunohistochemical studies using antibodies to the amino-terminal domain of AR revealed that the proportion of AR positive tumour cells varied among prostate cancers; poorly differentiated prostate cancers tended to have a diminished proportion of AR positive tumour cells (Ruizeveld de Winter et al 1990;Masai et al 1990). In ligand binding studies on tumour cytosols, Gorelic et al (1987) similarly noted heterogeneity of AR expression Correspondence to: T.H.…”
Section: Introductionsupporting
confidence: 69%
“…These authors used antibody ANI-15 for detection of AR. The reactivity of this antibody with the nuclei of basal cells lining the prostatic glands, as reported by Masai et al (1990), contrasts with the reactivity pattern of antibody F39.4 . In addition, differences in tissue processing and in the double-immunostaining technique may help to explain the discrepancy of the findings reported by these authors.…”
Section: Discussionmentioning
confidence: 51%
“…Most studies in the human report AR expression is restricted to the luminal cell layer; several studies in the mouse report widespread expression in both basal and luminal cells (16)(17)(18). qPCR and Western blot analyses demonstrate that both mRNA and protein for AR can be identified at high levels in basal/stem, luminal, and stromal cell fractions ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Similar observation was reported by several other authors. 12,[21][22][23] In a prostate cancer specimen, AR staining in the epithelium is heterogenous, with a marked decrease in ARpositive cells occurring in less differentiated tumors. 24 The possibility that increased heterogeneity of cellular staining may be present during hormonal therapy arose from our data.…”
Section: Discussionmentioning
confidence: 99%